2019
DOI: 10.1109/access.2019.2944631
|View full text |Cite
|
Sign up to set email alerts
|

Fully Secure Lightweight Certificateless Signature Scheme for IIoT

Abstract: In recent years, Industrial Internet of Things (IIoT) has become increasingly important for applications in the industry. Inevitably, security for IIoT has become a priority in order to deploy secure applications. Amongst available cryptographic tools, certificateless signature schemes offer sound authentication solutions and avoid public-key certification from Trusted Third Parties (TTP). Certificateless signatures solve the key escrow problem against the dishonest Private Key Generator (PKG) and has consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…However, the security complexity of the proposed scheme was based on the concept of elliptic curve cryptography. Later in 2019, Rezaeibagha et al [49], also improved the given scheme of Karati et al [46] by tossing a new scheme for the IIoT domain. However, the security complexity of the proposed scheme was based on the concept of bilinear pairing.…”
Section: B Certificateless Signature Schemesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the security complexity of the proposed scheme was based on the concept of elliptic curve cryptography. Later in 2019, Rezaeibagha et al [49], also improved the given scheme of Karati et al [46] by tossing a new scheme for the IIoT domain. However, the security complexity of the proposed scheme was based on the concept of bilinear pairing.…”
Section: B Certificateless Signature Schemesmentioning
confidence: 99%
“…To assess the impact, the given scheme was compared with seven relevant schemes proposed by Yeh et al [45], Karati et al [46], Zhang et al [47], Sajid et al [37], Nasrollah and Vanda [48], Rezaeibagha et al [49] and Thumbur et al [50]. The key points from our comparison are explained in Table 4.…”
Section: A Computation Costmentioning
confidence: 99%
See 1 more Smart Citation
“…Rezaeibagha et al [11] proposed a new lightweight CLS scheme for Industrial Internet of Things (IIoT). They proved its unforgeability for the Type I and II adversities under the hardness assumption of the q-BSDH problem.…”
Section: Vulnerabilities Of Two Cls Schemes From Pairingsmentioning
confidence: 99%
“…They showed that their scheme was existential unforgeable for Type I, Type II and Type III adversaries under the intractability of the SIS problem. Recently, Wang et al [17] proposed a certificateless aggregate signature (CLAS) scheme from bilinear pairings and Rezaeibagha et al [11] proposed a new lightweight CLS scheme for Industrial Internet of Things from bilinear pairings. The security of their schemes was proven for Type I and Type II adversaries under the intractability of some mathematical problems.…”
Section: Introductionmentioning
confidence: 99%